T-cell exhaustion in allograft rejection and tolerance. Issue 1 (February 2015) - Thorp, Edward B.; Stehlik, Christian; Ansari, M. Javeed
Abstract : Purpose of review: The role of T-cell exhaustion in the failure of clearance of viral infections and tumors is well established. There are several ongoing trials to reverse T-cell exhaustion for treatment of chronic viral infections and tumors. The mechanisms leading to T-cell exhaustion and its role in transplantation, however, are only beginning to be appreciated and are the focus of the present review. Recent findings: Exhausted T cells exhibit a distinct molecular profile reflecting combinatorial mechanisms involving the interaction of multiple transcription factors important in control of cell metabolism, acquisition of effector function and memory capacity. Change of microenvironmental cues and limiting leukocyte recruitment can modulate T-cell exhaustion. Impaired leukocyte recruitment induces T-cell exhaustion and prevents allograft rejection. Summary: Preventing or reversing T-cell exhaustion may lead to prevention of transplant tolerance or triggering of rejection; therefore, caution should be exercised in the use of agents blocking inhibitory receptors for the treatment of chronic viral infections or tumors in transplant recipients. Further definition of the role of T-cell exhaustion in clinical transplantation and an understanding of the mechanisms of induction of T-cell exhaustion are needed to develop strategies for preventing allograft rejection and induction of tolerance.